Challenges for research and prevention in relation to work and cardiovascular diseases - Kristensen, Tage S. (Scandinavian Journal of Work, Environment & Health, 1999)
The purpose of this paper is to discuss future challenges for research and prevention in the field of work environment and cardiovascular diseases (CVD). First, research on CVD and work during the last half of the 20th century is discussed. Second, the theories dominating the last 20 years are presented. Third, cardiovascular and occupational epidemiology are compared, and it is stressed that occupational epidemiology should avoid the individualistic bias of mainstream cardiovascular epidemiology. Finally, future challenges are discussed, and improvements are recommended concerning the use of intermediate end points, intervention research, theories about chemical and physical risk factors, the use of a unifying model for society, stress, and health, and the application of integrated prevention. It is concluded that research on CVD and work can play an important part in the development of integrated prevention strategies for the next century.
Keywords: epidemiologic method; IHD; ischemic heart disease; pshychosocial factor; review; stress